Vitis vinifera lipoxygenase LoxA is an allosteric dimer activated by lipidic surfaces - Pilati, Stefania; Wild, Klemens; Gumiero, Andrea; Holdermann, Iris Valerie; Hackmann, Yvonne; Serra, Mauro Dalla; Guella, Graziano; Moser, Claudio; Sinning, Irmgard (Journal of molecular biology, 2024)
Lipoxygenases catalyze the peroxidation of poly-unsaturated fatty acid chains either free or esterified in membrane lipids. Vitis vinifera LoxA is transcriptionally induced at ripening onset and localizes at the inner chloroplast membrane where it is responsible for galactolipid regiospecific mono- and di-peroxidation. Here we present a kinetic and structural characterization of LoxA. Our X-ray structures reveal a constitutive dimer with detergent induced conformational changes affecting substrate binding and catalysis. In a closed conformation, a LID domain prevents substrate access to the catalytic site by steric hindrance. Detergent addition above the CMC destabilizes the LID and opens the dimer with both catalytic sites accessible from the same surface framed by the PLAT domains. As a consequence, detergent molecules occupy allosteric sites in the PLAT/catalytic domain interface. These structural changes are mirrored by increased enzymatic activity and positive cooperativity when the substrate is provided in micelles. The ability to interact with micelles is lost upon dimer destabilization by site-directed mutagenesis as assessed by tryptophan fluorescence. Our data allow to propose a model for protein activation at the membrane, classifying LoxA as an interfacial enzyme acting on fatty acid chains directly from the membrane similar to mammalian 15-LOX and 5-LOX.